Pengaruh Latihan Variasi Knee Tuck Jump Terhadap Peningkatan Tinggi Loncatan Pada Siswa Ekstrakurikuler Bola Voli Putra SMP Negeri 2 Kota Bengkulu: The Effectiveness of Knee Tuck Jump Variation Exercise on Increasing Jump Height in Male Volleyball Extracurricular Students at SMP Negeri 2 Bengkulu City - Raka Syahputra; Andes Permadi; Deliyanto (Universitas Bengkulu, 2023)
Abstract This study aimed to investigate the effectiveness of knee tuck jump variations on the jump height of male volleyball students’ extracurricular at SMP Negeri 2 Bengkulu City. The method of this study utilized an experimental method. The design of this study used a one group pretest-posttest design. By given the knee tuck jump variation exercise treatment to the sample of 30 people. The instrument for measure jump height was the vertical jump. The data analysis technique in this study used the t-test formula, with a significant level of = 0.05. The results of the study obtained that t arithmetic = 9.00 t table = 1.697. The calculation of the results stated that the value of t arithmetic was 9.00 > t table 1.697 with a level of = 0.05. In conclusion, there was a significant effect of knee tuck jump variations in the form of the jump height of male volleyball extracurricular students at SMP Negeri 2 Bengkulu City. Keywords: Volleyball, Knee Tuck Jump, High Jump